Germination of alfalfa (Medicago sativa L.) seeds in Desert soil after fertilization with raw and digested animal manure - Abubaker, Jamal; Abobaker, Abdelsalam; Essalem, Mohemed; Bertata, Najia (Journal of Aridland Agriculture, 2023)
Animal manure has been approved as an appropriate soil fertilizer. However, the effect on seed germination, growth, and yield of crops still needs more evaluation across various agricultural ecosystems. A germination experiment was conducted to evaluate the performance of raw and digested sheep and poultry manure on alfalfa (Medicago sativa L.) seed germination in desert soil. Four sowing dates were evaluated in the experiment, i.e. directly, 10, 20, and 30 days after soil fertilization. The fertilizers were applied at rates corresponding to 50 and 100 kg Tot N ha-1. In addition, the response of germination to seed inoculation method was also assessed (Arabic gum as an adhesive solution and sawdust as a seed coating material). The germination was evaluated by determining seed germination time (SGT), time to reach maximum germination (TMG), germination index (GI), and final germination percentage (FGP). The results showed that sown seeds directly after fertilization with raw/digested sheep or poultry manure reduced and delayed seed germination. This was confirmed by all germination indices, long SGT, long TMG, low GI values, and a reduction in FGP. Moreover, when the seeds were sown 10 days after fertilization, all germination attributes were significantly (p<0.05) improved. Furthermore, the results revealed that the inoculation method used in the study had a positive effect on seed germination. To achieve better germination when using animal manure (raw or digested) as soil fertilizer, it is recommended to sow alfalfa seed 10 days after soil fertilization. Moreover, inoculating the seeds using Arabic gum as an adhesive solution and sawdust as a seed coating enhances germination in fertilized soil.